Logos and Education: On the Educational Philosophy of Heraclitus - Tasdelen, Vefa (KAMLA-RAJ ENTERPRISES, 2014)
In addition to antique disciplines such as ontology, epistemology and ethics, philosophy also contains relatively new disciplines such as linguistic philosophy and educational philosophy. Educational philosophy meets its most explicit definition in one of the contemporary philosophers of education like John Dewey's works. Added to that just as the case in the complete disciplines of philosophy, educational philosophy also bears a history that can be traced back to the birth of the origin of philosophy. This history deals with the studies of its specific problems, formulating its concepts and the realm of self-generating. With respect to the conceptual structure it displays and the contribution it renders to the next educational thinking, it can be argued that within Western philosophical tradition Heraclitus is among the forerunners of educational philosophy. The conceptual structure Heraclitus posited has been so influential that although very few fragments could reach to the ensuing ages, his teachings still preserve their huge impact. The concepts such as logos, change, motion, dialectic which are all widely inclusive and explanatory all occupy a unique position within the history of philosophy. Besides, the present article attempts to analyze Heraclitus' educational philosophy within the framework of the logos concept.
Keywords: Educational Philosophy; Heraclitus; Logos; Wisdom; Self; Ethics; Anthropology; Science & Technology - Other Topics; Social Sciences - Other Topics